2019
DOI: 10.3389/feart.2019.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obliquity of Slip in Normal Faults on Distribution of Open Fractures

Abstract: Close to surface, cohesive rocks fail in extension, which results in open fractures that can be several tens of meters wide, so-called massively dilatant faults. These open fractures make fault slip analysis in rifts challenging, as kinematic markers are absent. Faults in rifts often have oblique slip kinematics; however, how the amount of obliquity is expressed in the surface structure of massively dilatant faults remains enigmatic. Furthermore, the structures of oblique dilatant faults at depth is largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 97 publications
1
27
0
Order By: Relevance
“…21). The straight lines 10 plotted in the figure represent the relationship between vertical offset and horizontal opening corresponding to a simple dilatant normal fault at depth with dips ranging between 60°and 70°, being within the dip range as commonly inferred for Iceland (Angelier et al, 1997;Grant and Kattenhorn, 2004;Gudmundsson, 1992;von Hagke et al, 2019;Trippanera et al, 2015). We further define the parameter R as ratio of opening width and vertical offset as Eq.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…21). The straight lines 10 plotted in the figure represent the relationship between vertical offset and horizontal opening corresponding to a simple dilatant normal fault at depth with dips ranging between 60°and 70°, being within the dip range as commonly inferred for Iceland (Angelier et al, 1997;Grant and Kattenhorn, 2004;Gudmundsson, 1992;von Hagke et al, 2019;Trippanera et al, 2015). We further define the parameter R as ratio of opening width and vertical offset as Eq.…”
Section: Discussionmentioning
confidence: 98%
“…3a). Fissures can be 15 early stages of MDF or represent the lateral ends of MDF, which show en échelon fracturing when formed at oblique slip (Acocella et al, 2003;Grant and Kattenhorn, 2004;Gudmundsson, 1987a;von Hagke et al, 2019). Viewed in our DEMs (Fig.…”
Section: ) Fissuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Geological observations in actively rifting regions such as Iceland and analogue modelling studies (e.g. van Gent et al 2010;von Hagke et al 2019) have shown that highly dilated and interconnected fissure systems can form in mechanically strong basement rocks, such as charnockite, granite and basalt, during active extensional faulting as stresses become tensile in the uppermost crust. Thus subvertical open fissures in the upper few hundred metres closest to the surface pass down at greater depths into normal fault shear fractures dipping at c. 60°at depth (Fig.…”
Section: Implications For Development Of the Hydrocarbon Reservoirmentioning
confidence: 99%
“…Iceland is a volcanic island in the Atlantic Ocean on the Mid-Atlantic Ridge separating the Eurasian and North American plates. It is linked to a deep mantle plume (Einarsson, 1991;Lawver and Muller, 1994;Vink, 1984;Wolfe et al, 1997), with associated melt production forming the Icelandic shelf (Brandsdóttir et al, 2015) with a local crustal thickness of at least 25 km (Allen et al, 2002). It is located between the Reykjanes Ridge segment in the SW and the Kolbeinsey Ridge in the north (Fig.…”
Section: Geological Background and Study Sitesmentioning
confidence: 99%